OP24 Efficacy and safety of upadacitinib induction therapy in patients with Moderately to Severely Active Ulcerative Colitis: Results from the phase 3 U-ACHIEVE study. (27th May 2021) - Danese, S; Vermeire, S; Zhou, W; Pangan, A; Siffledeen, J; Hébuterne, X; Nakase, H; Higgins, P; Chen, M H; Sanchez-Gonzalez, Y; Huang, B; Xie, W; et al.
Abstract: Background: An unmet therapeutic need remains in patients with ulcerative colitis (UC). U-ACHIEVE is one of two phase 3 induction trials evaluating the safety and efficacy of the selective Janus kinase–1 inhibitor upadacitinib (UPA) 45 mg once daily (QD) in adults with UC. Methods: U-ACHIEVE is a multicentre, double-blind, placebo (PBO)–controlled trial (NCT02819635) that randomized patients with moderately to severely active UC 2:1 to UPA 45 mg QD or PBO for 8 weeks. Patients were stratified by response to biologic therapy (inadequate vs non–inadequate responder), baseline corticosteroid use (yes or no), and baseline adapted Mayo score (≤7 or >7). The primary endpoint was proportion of patients achieving clinical remission (per adapted Mayo Score) at week 8.Ranked secondary endpoints included endoscopic improvement, endoscopic remission, and clinical response per adapted Mayo Score at week 8; clinical response per partial adapted Mayo Score at week 2; and histologic-endoscopic mucosal improvement at week 8. Non-responder imputation incorporating multiple imputations for missing data due to COVID-19 are reported. Safety was assessed through week 8. Results: 474 patients were randomized (UPA, n=319; PBO, n=155). Baseline characteristics were well balanced between groups (Table 1 ). A significantly higher proportion of patients receiving UPA (26.1%) vs PBO (4.8%) achieved clinical remission at week 8 (adjusted treatment difference [95% CI], 21.6% [15.8, 27. 4 ]; P <0.001; Figure 1 ). For all ranked secondary endpoints, UPA was superior to PBO ( P <0.001; Figure 1 ). A significant difference in clinical response favouring UPA vs PBO was seen as early as week 2 (60.1% vs 27.3%) and was sustained over 8 weeks (79.0% vs 41.6%; Figure 2 ). There were more serious adverse events (AEs), severe AEs, and AEs leading to study drug discontinuation with PBO (Table 2 ). The most common AEs were acne, creatine phosphokinase elevation, and nasopharyngitis with UPA and worsening of UC and anaemia with PBO. Incidence of serious infection was similar between UPA and PBO. Neutropenia and lymphopenia were reported more frequently with UPA vs PBO (Table 2 ).No adjudicated gastrointestinal perforation, major cardiovascular AEs, or thrombotic events and no active tuberculosis, malignancy, or deaths were reported. Conclusion: In patients with moderately to severely active UC, UPA 45 mg QD induction therapy was superior to PBO in inducing clinical remission/response, and endoscopic remission/response over 8 weeks; responses were significant and rapid. UPA 45 mg QD was well tolerated; safety was comparable with the known safety profile of UPA, and no new safety signals were identified.